Makalah uin - Rahayu, Winda (Prosiding SI MaNIs (Seminar Nasional Integrasi Matematika dan Nilai-Nilai Islami), 2017)
Mastery of concept is an abstract idea and categorized into the objects .. To achieve maximum learning outcomes mastery of mathematical concepts need to be improved. The purpose of this study are: (1) to know the mastery of the concept of mathematical proficiency of students who have high logical intelligence using scientific approach , (2) To know mastery of mathematical concepts of students who have logical intelligence is using scientific approach, (3) To know mastery of mathematical concepts that have low logical intelligence using scientific approach This research is a qualitative research. Research instruments used are test, observation sheet And interviews.Tes used to know mathematical logical intelligence.After the test results are analyzed then conducted interviews to students who have high, medium and low category.Results of this study are students who have high logical intelligence, moderate And low has a different mastery of concepts.